2015
DOI: 10.1371/journal.pone.0120176
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Caspase Activation Promotes Generation of Cardiomyocytes from Embryonic Stem Cells

Abstract: Generation of new cardiomyocytes is critical for cardiac repair following myocardial injury, but which kind of stimuli is most important for cardiomyocyte regeneration is still unclear. Here we explore if apoptotic stimuli, manifested through caspase activation, influences cardiac progenitor up-regulation and cardiomyocyte differentiation. Using mouse embryonic stem cells as a cellular model, we show that sublethal activation of caspases increases the yield of cardiomyocytes while concurrently promoting the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 35 publications
1
26
2
Order By: Relevance
“…The expression of typical CM genes (including transcription factors, specific structural genes, and ionic channels) were revealed to be significantly higher in stored hiPSC‐CMs than in the control, suggesting that the hypothermia state may enhance CM enrichment/maturation processes. A recent study reported that apoptotic stimuli—more specifically, a sublethal caspase‐activation—up‐regulates cardiac progenitor and CM differentiation, increasing the final yield of CMs [56]. As shown in our study and in others [16, 37, 57], the hypothermic state promotes caspase activation; consequently, we could also speculate about an interference of cold preservation in cardiogenic pathways.…”
Section: Discussionsupporting
confidence: 80%
“…The expression of typical CM genes (including transcription factors, specific structural genes, and ionic channels) were revealed to be significantly higher in stored hiPSC‐CMs than in the control, suggesting that the hypothermia state may enhance CM enrichment/maturation processes. A recent study reported that apoptotic stimuli—more specifically, a sublethal caspase‐activation—up‐regulates cardiac progenitor and CM differentiation, increasing the final yield of CMs [56]. As shown in our study and in others [16, 37, 57], the hypothermic state promotes caspase activation; consequently, we could also speculate about an interference of cold preservation in cardiogenic pathways.…”
Section: Discussionsupporting
confidence: 80%
“…Recent studies suggest that sublethal caspase activation in murine-ESCs promotes the proliferation and differentiation of c-Kit + /α-actinin low cardiac progenitor cells [37] . Reciprocally, caspase inhibition dramatically reduces the amount of differentiated cardiomyocytes [37] .…”
Section: Caspase Roles In Embryonic and Induced Pluripotent Stem Cellmentioning
confidence: 99%
“…A similar observation was evident in hPSC-CMs stored under hypothermic conditions (+4°C), with the expression of several cardiomyocyte-specific genes including MLC2V significantly upregulated (Correia et al, 2016). The exact mechanism by which cold preservation could induce hPSC-CM maturation is unclear but hypothermic storage does increase caspase activity which has been demonstrated to promote the differentiation of mouse embryonic stem cell (ESC)-derived cardiac progenitors (Bulatovic et al, 2015). Alternatively, exposure of the hPSC-CMs to DMSO may also contribute to the enrichment in ventricular cardiomyocytes.…”
Section: Discussionmentioning
confidence: 55%